KEPADATAN, MORFOMETRIK DAN POLA DISTRIBUSI UDANG MANTIS Harpiosquilla raphidea DI PERAIRAN ESTUARI KARANG GADING - Pane, Safitri Febriani; Mulya, Miswar Budi; Barus, Ternala Alexander (Scripta Biologica, 2023)
Mantis shrimp, Harpiosquilla raphidea, an economically important commodity in Karang Gading, Deli Serdang, is at risk of population decline owing to uncontrolled fishing. This study was conducted to analyze population density, morphometric characteristics, distribution patterns, and correlations between physicochemical parameters and mantis shrimp density. The research was conducted in the Karang Gading wildlife sanctuary of Deli Serdang from July to September 2021, with sampling performed at three stations chosen by purposive random sampling. The total number of mantis shrimp individuals caught was 66, with a density of 4,83 ind/m2, on station 2 of 3,83 ind/m2, and station 3 of 2,33 ind/m2. Morphometric characters that have a strongly correlated effect were found in station 2 (total length with carapace length), a weakly correlated was obtained at station 1 (total length with carapace length), station 2 (total length with abdominal width, total length with telson width and total length with propodus length), station 3 (total length with carapace length, total length with abdominal width, total length with telson width and total length with propodus length) and moderately correlated was obtained at station 1 (total length with abdominal width, total length with telson width and total length with propodus length), all relationships between morphometric characters showed negative allometric growth patterns. The relationship between the total length and weight was obtained by the value of b < 3, which is a negative allometric. The distribution patterns at each station were categorized as grouped and unified, with an Id value of 0,791 – 1,004. The analysis results that strongly correlated and valued positively were salinity, current speed, and Dissolved Oxygen (DO); those with strong correlation and negative values were temperature, water brightness, and BOD5; moderately correlated and valued positively were pH and nitrate; strongly correlated and negatively valued (water depth); and weakly correlated and negative (phosphate).